Account of Ebenezer Sproat - Sproat, Ebenezer
Official financial report covering the period from June 30, 1794, through December 31, 1808, signed February 4, 1809.
U.S. inspector of revenues.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Revenue -- United States; Public officials